Islamic Social Business: The Role of al-Qardul Hasan in Empowering Vulnerable Micro-Enterprises through Bankziska - Adi Santoso; Yuyun Ristianawati; Sri Hartono; Fanji Farman; Ina Nusuki (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study examines the development and implementation of Islamic financial institutions based on Al-Qardul Hasan, specifically through the Bankziska model, in the context of empowering micro, small, and medium enterprises (MSMEs). The phenomenon underlying this research is the high dependence of MSMEs on loan sharks who provide high-interest loans, especially in traditional markets, rural areas, and poor urban areas. In addition, the difficulty of accessing finance from conventional and Islamic banks further exacerbates the economic conditions of MSMEs. The Bankziska concept offers an alternative solution by providing loans without interest, without administrative fees, without fines, and collateral. Bankziska utilizes zakat, infaq, shodaqoh, and other social and religious funds to support MSMEs. The main objective of this concept is to realize a prosperous and just society (Baldatun thayyibatun wa rabbun ghafur). The research method used is qualitative with a case study approach. The research results indicate that the Bankziska concept can serve as an alternative model for empowering MSMEs based on Sharia principles, reducing dependence on loan sharks, and increasing financial access for MSMEs. Implications of this research include the development of a more inclusive and sustainable Sharia financial business model.